Education and family bias: an approach to the vulnerability of married women in Spain, 2005-2012 - Juan A. CAÑADA VICINAY (Ediciones Universidad de Salamanca, 2016)
The purpose of this paper is to analyze the role of education in labor inequality based on gender, age and marital status in Spain in the period 2005q1-2012q4 with individual data from the EPA. The axes of inquiry are twofold: 1st) crosssectional approach to family bias expressed in the job profiles of cycle life, occupational segregation, concentration of employment in occupational groups and allocation of family responsibilities between spouses; and 2nd) longitudinal treatment with sliding panel of family interference in the market status of married women by age and educational level. Cross-sectional analysis shows negative associations between marriage-education in both sexes and between education and participation in women by comparison with men, jointly with large gender segregation in married women suggests that they support a family specific bias which hinders its market presence. The individual perception of family interference confirms this fact as they are married women who suffer mainly from the problems of work-family conciliation, even younger than 44 years where they are more educated than their husbands and gender equality is a social value settled. The longitudinal analysis quantifies, with multinomial Logit estimates, the disadvantage of married women to participate into the market in terms of the entry barrier for inactive wives and the premature withdrawal for occupied ones due to problems of work-family reconciliation. In short, family responsibilities leave off the market to married women, regardless of age and education.